(3CMGSf GdeMGSfs - (3EHQGgje Hf CMeO Hf eMeO GdMfHdj, GHf eYGdj GdQbj, HQgGf GdOjf CHh ESMGb , J (B703 (3g`s; (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL,J (B597 (3g` s ((3CMeO Hf Ndjd GdLfjfi s)
(3ChdgG (B:s
(3gPG GdcJGH GNJQJ ajg CMSf eG ai cJGH UahI GdUahI dCHi GdaQL Hf GdLhRi s
(3BNQgG (B:s
(3GdG HfjI UZjQI aEfgG HcJ abjd dgG eG jHcjc bGdJ eNdhb fXQ EdjfG aGSJZfjfG acja dh fXQ EdjfG GdNGdb s
(3fSNI KGdKI ecedI ef ChdgG HNW MOjKs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs